The morphological characteristics of frozen bull sperm of different breeds the Bank of genetic resources the long-term storage in liquid nitrogen were studied. A significant difference between the indicators of pathological and dead forms of bull semen wi - Ляшенко, А. О. (Scientific Progress & Innovations, 2018)
The morphological characteristics of frozen bull sperm of different breeds the Bank of genetic resources the long-term storage in liquid nitrogen were studied. A significant difference between the indicators of pathological and dead forms of bull semen with different terms of storage was set. The result studies, by the terms of storage 10-45 years, in bulls of dairy breeds were observed above normal ​​of pathological forms of sperm in an average of 2,5 %, except for sperm Ukrainian Black Pied dairy breed. In semen bulls of Simmental and beef breeds above an average of 5 %.